2022
DOI: 10.3390/biom12020236
|View full text |Cite
|
Sign up to set email alerts
|

Spexin Regulates Hypothalamic Leptin Action on Feeding Behavior

Abstract: Spexin (SPX) is a recently identified neuropeptide that is believed to play an important role in the regulation of energy homeostasis. Here, we describe a mediating function of SPX in hypothalamic leptin action. Intracerebroventricular (icv) SPX administration induced a decrease in food intake and body weight gain. SPX was found to be expressed in cells expressing leptin receptor ObRb in the mouse hypothalamus. In line with this finding, icv leptin injection increased SPX mRNA in the ObRb-positive cells of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 62 publications
2
8
0
Order By: Relevance
“…Similarly, as shown in Figure 4D, LE supplementation stimulated mRNA expression of spexin which is recently identified neuropeptide involving in energy homeostasis and POMC gene expression (46). Previous research reported that spexin regulated hypothalamic leptin action on POMC gene expression and consequently modulated feeding behavior (46). Thus, our data suggest that LE supplementation can promote anorexigenic signal through POMC neuronal activity in hypothalamus.…”
Section: Discussionsupporting
confidence: 78%
“…Similarly, as shown in Figure 4D, LE supplementation stimulated mRNA expression of spexin which is recently identified neuropeptide involving in energy homeostasis and POMC gene expression (46). Previous research reported that spexin regulated hypothalamic leptin action on POMC gene expression and consequently modulated feeding behavior (46). Thus, our data suggest that LE supplementation can promote anorexigenic signal through POMC neuronal activity in hypothalamus.…”
Section: Discussionsupporting
confidence: 78%
“…We found that the body weights of the control mice injected with vehicle were lower compared to the control mice before injection, which may be resulted from short-term stresses of the animals induced by vehicle injection. This opinion is evidenced by a previous report that the body weights of the mice decreased upon saline injection [63]. It is known that STAT3 in the hypothalamic POMC neuron is a key element of leptin’s action to control appetite and energy homeostasis [28, 30, 53], and phosphorylation at Y705 for activation of hypothalamic STAT3 has been documented to contribute to leptin signaling pathway [30, 44, 64, 65].…”
Section: Discussionmentioning
confidence: 80%
“…The novel neuropeptide SPX acts as an important factor in regulating feeding behavior [ 25 , 26 ], long-chain fatty acid uptake [ 27 ], energy utilization [ 27 , 28 ], and body weight regulation [ 29 , 30 ]. Bile acids also show a mediatory role in lipid metabolism and energy balance [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%